Bullous dermatitis of the right hemisoma in left-handed. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
You have to think of a possible dermatitis artefacta when the history and physical examination are not reminiscent of any known skin disorder. In this case the history did not show any infectious, drug or exogenous factor and showed the spontaneous and quick regression of the lesions. The physical examination showed lesions only on the right hemisoma but without a metameric distribution or along the lines of Blaschko. Another finding suggesting dermatitis artefacta is the presence of lesions in exposed and then visible sites; in our case the lesions were present in covered but easily accessible sites. The finding that reinforced the hypothesis of dermatitis artefacta was the presence of lesions only on the right hemisoma in a left-handed guy. Once you make the diagnosis of dermatitis artefacta it is useless to discover the precise causal mechanisms; on the other hand, it is important with the help of the psychologist to overcome the basic imbalance of the patient.